HUBUNGAN DIABETES MELITUS DENGAN KEJADIAN STROKE ISKEMIK DI RSUD DR. MOEWARDI SURAKARTA TAHUN 2010 - Aulya Farra Ramadany; Listyo Asist Pujarini; Anika Candrasari (Biomedika, 2013)
From survey at Dr. Moewardi Hospital in the year 2010, the incidence of stroke patients increase 5-7% every year. Diabetes mellitus has a relationship with ischemic stroke through aterosklerosis. However, the relationship of diabetes mellitus as a risk of ischemic stroke remains uncertain due to diabetes is not a single factor for stroke. Research aim was to determine the relationship between the incidence of diabetes mellitus and ischemic stroke. It was conducted at the neurologi unit in Dr.Moewardi Hospital Surakarta, the design was a cross sectional with sample size of 132 people. The sampling technique used simple random sampling. The result is the number of ischemic stroke patients with diabetes mellitus by 47 people (71.21%). From chi square analysis (x 2) x 2 = 13.516 obtained and p 0.000 with a value of OR = 3.8 and IK = 1.841 to 7.869. Its mean that there was a relationship between diabetes mellitus and incident ischemic stroke and people with diabetes mellitus have a risk 3,8 more times will got stroke ischemic than people without diabetes mellitus.Keywords: diabetes mellitus, ischemic, stroke